Preference of e-bike by women in India–a niche market for auto manufacturers - Alamelu, Ramachandran; Anushan, Chandrasekaran Sivasundaram; Selvabaskar, Sivasankara Gandhi (Business: Theory and Practice, 2015)
The increasing urbanization with climate change, global warming issues and the related need to decarbonize the economy, is forcing urgency for identifying the alternate source for the global adoption and sustainable scalable solutions. The country’s demographic and road patterns and its natural resources availability provide enormous scope for the electric bike industry. As per the “Navigant Research Report”, it is predicted that by 2018, the sales of electric vehicles in India will shoot up by 17 percent. 1.1 million electric vehicles will be targeted within next five years. A recent study on the environment impact of e-bikes with other forms of transportation found that e-bikes are about 18 times more energy consumption than SUV, 13 times than a sedan, 6 times more than rail transit, and it is having considered as an innovated conventional bicycle. It is a frugal innovation strategy which provide safe carbon free environment, and moreover a part of health rehabilitation programmes. It is required that societal, economic and political and infrastructure systems integrate together to balance the energy environment. With this potential, the era of electric bike started its new avenues on the roads of India specifically focusing on Indian women. To develop this viewpoint, the present study focuses on the preference of e-bike among the women in Madurai city.